The fiscal crisis of states and the fiscal recovery regime: The federative déjà vu - Torrezan, Raphael Guilherme Araujo [UNESP]; de Paiva, Cláudio César [UNESP] (FapUNIFESP (SciELO), 2021)
This article aims to discuss the fiscal crisis of the Brazilian states and the Fiscal Recovery Regime (FRR) enacted in 2017, whose adjustment measures are considered fundamental for the balance of state public accounts. Under the federative perspective, these adjustments represent a weakening of the states since such measures affect their political and administrative autonomy. The state of Rio de Janeiro was chosen as the subject of this research because it was the only state to join the FRR since its enactment, and the study used data from the years 2008 to 2019. The findings suggest that the austerity measures adopted by the state of Rio de Janeiro were not enough to guarantee financial stability and the rebalancing of public accounts. Among the results, we highlight that the state remained financially insolvent and the indebtedness for the period grew. The only positive result within the terms of the FRR was the reduction in the state’s personnel expenses. Finally, it is noted that until the penultimate quarter of 2019, the state of Rio de Janeiro did not comply with the terms of the agreement signed with the federal government.
La crisis fiscal de los estados brasileños y el régimen de recuperación fiscal: El déjà vu federativo
A crise fiscal dos estados e o regime de recuperação fiscal: O déjà vu federativo
Keywords: Crisis of states; Fiscal federalism; Fiscal recovery regime